Posttranslational Modifications of Pyruvate Kinase M2: Tweaks that Benefit Cancer - Prakasam, Gopinath; Iqbal, Mohammad Askandar; Bamezai, Rameshwar N. K.; Mazurek, Sybille (Frontiers in Oncology, 2018)
Cancer cells rewire metabolism to meet biosynthetic and energetic demands. The characteristic increase in glycolysis i.e. Warburg effect, now considered as a hallmark, supports cancer in various ways. To attain such metabolic reshuffle, cancer cells preferentially re-express the M2 isoform of pyruvate kinase (PKM2, M2-PK) and alter its quaternary structure to generate less-active PKM2 dimers. The relatively inactive dimers cause the accumulation of glycolytic intermediates that are redirected into anabolic pathways. In addition, dimeric PKM2 also benefits cancer cells through variety of non-glycolytic moonlight functions, such as gene transcription, protein kinase activity and redox balance. A large body of data has shown that several distinct post-translation modifications regulate PKM2 in a way that benefits cancer growth, e.g. formation of PKM2 dimers. This review discusses the recent advancements in our understanding of the variety of post-translation modifications (PTMs) and the benefits they impart to the sustenance of cancer. Understanding the PTMs in PKM2 is crucial to assess their therapeutic potential and to design novel anti-cancer strategies.